Continuous Restoration Procedure of Current State of Linear Ordinary System on Incomplete Output - A. V. Metelskii; S. A. Minjuk (Наука и техника)
The paper considers a problem of observation for the named system as it is interpreted by N.N. Krasovskii. The paper shows how to construct linear continuous operation of restoration of the current system state in accordance with the known output.